2012
DOI: 10.1016/j.jcps.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Does time fly when you're counting down? The effect of counting direction on subjective time judgment

Abstract: We show that counting downward while performing a task shortens the perceived duration of the task compared to counting upward. People perceive that less time has elapsed when they were counting downward versus upward while using a product (Studies 1 and 3) or watching geometrical shapes (Study 2). The counting direction effect is obtained using both prospective and retrospective time judgments (Study 3), but only when the count range begins with the number “1” (Study 2). Furthermore, the counting direction af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…For example, people feel that future events are subjectively closer than past events (Caruso, Van Boven, Chin, & Ward, 2013). Time appears to pass faster when people are counting down to zero compared with when they counting up, without a definite upper bound (Shalev & Morwitz, 2013). In a related domain, Van Kerckhove, Geuens, and Vermeir (2015) found that an object 190 cm from people’s eyes was estimated to be 169 cm away when it was below eye level (looking downward), but 231 cm away when it was above eye level (looking upward).…”
Section: Discussionmentioning
confidence: 99%
“…For example, people feel that future events are subjectively closer than past events (Caruso, Van Boven, Chin, & Ward, 2013). Time appears to pass faster when people are counting down to zero compared with when they counting up, without a definite upper bound (Shalev & Morwitz, 2013). In a related domain, Van Kerckhove, Geuens, and Vermeir (2015) found that an object 190 cm from people’s eyes was estimated to be 169 cm away when it was below eye level (looking downward), but 231 cm away when it was above eye level (looking upward).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one reason why quantity scarcity marketing tactics increase sales is because they increase arousal (Zhu and Ratner 2015, Study 3). Relevant to the current research, as time to obtain the promotion diminishes, consumers experience time as increasingly short, which prompts greater arousal (Shalev and Morwitz 2013). Thus, we propose that although exogeneous justification for online time scarcity promotions will decrease the activation of persuasion knowledge, lowering the likelihood that time scarcity will yield negative effects on consumer interest, the highest likelihood for positive effects of such tactics exists when the time remaining until the deal expires is shorter as opposed to longer.…”
Section: Theoretical Explanation: the Relevance Of Persuasion Knowledgementioning
confidence: 86%
“…Differences in arousal across retail contexts suggest a third potential direction for future research. Although prior work shows that the amount of time left on a timer alters arousal (e.g., Shalev and Morwitz 2013), other attempts to boost arousal may be less uniform in their results. Different consumers may vary in their subjective interpretation of arousal levels (Kuppens et al 2013), suggesting that arousal-inducing mechanisms, such as dynamic countdown timers, can impact process satisfaction in unpredictable ways.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…(2013), Shalev and Morwitz (2013) and Fraisse (1984) Inactivity during waiting time Waiting time without activity is overestimated. Lee et al (2012), LeBoeuf and Simmons (2007), Zakay (2000Zakay ( , 2005, Durrande-Moreau (1999), Taylor (1994) and Hornik (1984) Routine activities and skills Some routine tasks require shorter durations to be completed but lead to a feeling of longer duration.…”
Section: Midway Between the Context And The Individualmentioning
confidence: 99%
“…From a perspective that may seem contradictory, Jia et al (2013) indicated that, unlike the retrospective estimate of duration, which tends to be overestimated, the duration of future activities is underestimated. Finally, Shalev and Morwitz (2013) pointed out that a countdown gives the impression of an acceleration of time and hence an underestimation of elapsed time. Another explanation, this time affective in nature, links the perception of duration to the emotions felt.…”
Section: Midway Between the Context And The Individualmentioning
confidence: 99%